2020
DOI: 10.1007/s40685-019-00106-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patterns of corporate social responsibility using a complementary K-means clustering criterion

Abstract: Companies’ objectives extend beyond mere profitability, to what is generally known as Corporate Social Responsibility (CSR). Empirical research effort of CSR is typically concentrated on a limited number of aspects. We focus on the whole set of CSR activities to identify any structure to that set. In this analysis, we take data from 1850 of the largest international companies via the conventional MSCI database and focus on four major dimensions of CSR: Environment, Social/Stakeholder, Labor, and Governance. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…One would expect that the CSP of large companies in this regard would be more consistent. Our results validate previous findings [63] that consider CSP to be a process of change that evolves from predominantly uniform patterns (using results from 2007) to the predominantly single-focus patterns of CSR (results from 2012). The authors consider that the identified patterns will evolve significantly as the external context changes (e.g., as a result of the COVID-19 crisis), and that the transition process will enable more sophisticated CSP practices in the future.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…One would expect that the CSP of large companies in this regard would be more consistent. Our results validate previous findings [63] that consider CSP to be a process of change that evolves from predominantly uniform patterns (using results from 2007) to the predominantly single-focus patterns of CSR (results from 2012). The authors consider that the identified patterns will evolve significantly as the external context changes (e.g., as a result of the COVID-19 crisis), and that the transition process will enable more sophisticated CSP practices in the future.…”
Section: Discussionsupporting
confidence: 90%
“…The cluster analysis theory enables the identification of different structural patterns of CSR activity along with its dimensions [63]. In the real world, some companies may focus on just one dimension, such as the environment ("going green") or labor (staff development); others might prefer to split their efforts by contributing equally to two or more dimensions [109].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Chae and Park [24], "structural topic modeling (STM)", a machine learning-based content analysis tool, is used to understand themes or subjects from CSR-related Twitter interactions. Taran and Mirkin [25] apply the popular approach of k-means clustering on the conventional Morgan Stanley Capital International (MSCI) database and focus on four primary dimensions of CSR: environment, social/stakeholder, labor, and governance. Castellanos et al [26] utilizes text data mining (TDM) to analyse the contents of Corporate Social Responsibility (CSR) reports.…”
Section: Introductionmentioning
confidence: 99%
“…Mallin et al (2013) argued that various types of stakeholders are exercising pressures on corporations to mitigate their negative impacts on societies and environment. In addition, many authors indicated the negative consequences may happen if a corporation fails to provide a satisfactory Corporate Social Responsibility Disclosure (CSRD) of its activities such as losing reputation, declining firm value and bad publicity (Peloza and Shang 2011;Taran and Mirkin, 2020). Accordingly, the significance of CSRD has been increased as a trigger that measures the corporate compliance towards the society and environment.…”
Section: Introductionmentioning
confidence: 99%